Answer:
None
Step-by-step explanation:
The answer would be 2 and 4 because if you added these two numbers together it would equal 6 and but if you subtracted 4 from 2 you would get -2. ex- if you have 4 dollars and you gave your friend those 4 dollars but the next day they payed you back 2 they would still need to give you back 2 dollars.
Answer:
x = 7
General Formulas and Concepts:
Order of Operations: BPEMDAS
Step-by-Step Explanation:
Step 1: Define
5(x - 3) = 2(x + 3)
Step 2: Solve for x
1. Distribute: 5x - 15 = 2x + 6
2. Subtract 2x on both sides: 3x - 15 = 6
3. Add 15 on both sides: 3x = 21
4. Divide both sides by 3: x = 7
9514 1404 393
Answer:
(x -y -1)(x +y)
Step-by-step explanation:
The expression can be factored by grouping.
x^2 -y^2 -x -y = (x^2 -y^2) -(x +y)
= (x -y)(x +y) -1(x +y)
= (x -y -1)(x +y)
_____
It is useful to know that a difference of squares is factored as ...
a^2 -b^2 = (a -b)(a +b)